Analytical validation of a scrape-free multitarget stool RNA test for colorectal cancer screening - Barnell, Erica K.; Kruse, Kimberly; Wurtzler, Elizabeth M.; Scott, Maya Crowder; Barnell, Andrew R.; Duncavage, Eric J. (Practical laboratory medicine, 2025)
Traditional stool-based colorectal cancer (CRC) screening tests require patients to collect and swab their own stool, which can reduce adherence due to aversion and introduce variability from user error. A novel multitarget stool RNA test (mt-sRNA, ColoSense) eliminates the need for scraping or swabbing stool. Instead, patients merely deposit and ship a sample to the lab. Once recieved, laboratory technologists swab the sample and quantify hemoglobin concentrations using the fecal immunochemical test (FIT). This study evaluates the reliability and reproducibility of this in-laboratory fecal sampling method. Analytical validation was performed by generating stool pools with known hemoglobin concentrations and exposing pools to various conditions prior to testing with the in-lab FIT. Analytical validation assessed freeze thaw stability, interfering substances, stool input volume, precision, and in-transit stability. Clinical equivalency was also evaluated. All studies met predefined acceptance criteria. The assay demonstrated stability for up to three freeze-thaw cycles. Interference testing with nine dietary substances showed no impact on assay performance. The in-lab FIT maintained accuracy across five different stool input volumes and demonstrated high precision. In-transit stability was confirmed for up to 120 hours, supporting sample robustness during shipping and handling. Clinical equivalency demonstrated in-lab FIT sensitivity of 78 % for CRC and 33 % for advanced adenomas, aligning with previously reported performance of the at-home FIT method. Analytical validation of the in-lab FIT demonstrates the reliability and robustness of this streamlined, single-sample collection method. This improvement could enhance adherence and patient ease-of-use in stool-based CRC screening.